Perlindungan Hukum Nasabah Bank Terhadap Kekeliruan Transfer Dana Akibat Kelalaian Bank - Ningtyas, Fona Aprilia Dwi; Permana, Bayu Indra (Journal of Economic and Business Law Review, 2023)
Fund transfers are a solution to the problem of sending money that requires people to carry money from one area to another and reduce the various risks that can occur when transferring money in cash. However, nowadays there are often cases of erroneous transfers of funds in the form of foreign incoming funds where the recipient feels he does not know the information about the sender of the funds, the funds come in suddenly where the recipient customer does not feel he is in or has made a transaction with another party which results in transfer of funds to the account. Cases of errors in customer fund transfers that occur can result in losses experienced and suffered by the customer concerned. This study uses a juridical-normative method, by collecting descriptions and information that can be used in resolving this problem using a statutory approach and a conceptual approach, as well as using sources of primary legal materials and secondary legal materials, as well as methods of collecting legal materials with literature studies. . The status of ownership of funds in a fund transfer is the right of the recipient of the funds as long as it can be proven that the funds are his right and are not an error in the transfer of funds. Meanwhile, this form of legal protection for errors in fund transfers can also be seen in the bank's responsibility to cancel or issue a new fund transfer order addressed to a recipient who is entitled to and desired by the sender. Keywords: Legal Protection, Confusion, Fund Transfers, Customers, Banks